The corrosion of an equimolar FeCoNiCrMn high-entropy alloy in various CO2/CO mixed gases at 700 and 950 °C. (June 2019) - Kai, W.; Chien, F.C.; Cheng, F.P.; Huang, R.T.; Kai, J.J.; Liu, C.T.
Highlights: The corrosion of FeCoNiCrMo high-entropy alloy was studied in CO2 /CO gas mixture at 700 and 950 °C. This high-entropy alloy experienced an exclusive oxidation in various CO2 /CO mixed gases. The oxidation rates steadily increased with increasing oxygen pressure and temperature. TEM analyses confirmed that (Mn, Fe)3 O4 and MnO formed in the outer layer while (Mn, Cr)3 O4 and MnO developed in the inner layer at 950 °C. Abstract: The corrosion behavior of an equimolar FeCoNiCrMn high-entropy alloy was studied in various combination of CO2 /COmixed gases at 700 and 950 °C, with the oxygen partial pressure range from 5.0 × 10 −16 to 7.9 × 10 −8 Pa. The alloy exclusively experienced oxidation, and its kinetics followed the parabolic rate law at both temperatures with the oxidation rates steadily increasing with oxygen pressure. This result demonstrated that a typical oxide scale exhibited a p-type semiconductivity. The scale formed on the alloy at 700 °C was thin, consisting of a mixture of MnO, (Mn, Fe)3 O4, and (Mn, Cr)3 O4, while the duplex scales formed at 950 °C consisted of an outer layer of (Mn, Fe)3 O4 and, MnO, and an inner layer of (Mn, Cr)3 O4 andMnO.